Evaluating The Communicative Approach in Arabic Language Learning: A Case Study at a Secondary School in Indonesia - Miftahul Mufid; Isnainiyah; Nurul Ainiy (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Learning Arabic in Indonesia is still focused on traditional methods that pay more attention to language structure (grammar-based) rather than the ability to communicate genuinely. The application of the communicative approach in this study aims to enhance the skill of oral communication. This study is a deep study on the implementation of the communicative curriculum in the two-year credit hour system program at Zain Al-Hassan Qanqoun Model High School. This research was characterized by revealing the limitations and opportunities to apply this curriculum within an intensive time frame, which has not been explicitly discussed in previous research. This study also assesses the difference in students’ achievement in a competitive learning environment with a heavy academic load.Methodology: The study adopted triangulation method technique. The data was obtained through deep interviews, direct observation, and document analysis.Findings: The results of the research showed that the communicative curriculum was able to drive an improvement in students’ abilities in speaking Arabic, but time constraints and imbalance in learning facilities constitute a major obstacle in the overall learning process.Implications/Novel Contribution: This study makes recommendations for improving the communicative curriculum in the context of the credit hour system, through adaptive pedagogical innovations more appropriate to dynamic educational situations.